2013
DOI: 10.1016/j.molimm.2012.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil rolling at high shear: Flattening, catch bond behavior, tethers and slings

Abstract: Neutrophil recruitment to sites of inflammation involves neutrophil rolling along the inflamed endothelium in the presence of shear stress imposed by blood flow. Neutrophil rolling in post-capillary venules in vivo is primarily mediated by P-selectin on the endothelium binding to P-selectin glycoprotein ligand-1 (PSGL-1) constitutively expressed on neutrophils. Blood flow exerts a hydrodynamic drag on the rolling neutrophil which is partially or fully balanced by the adhesive forces generated in the P-selectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 120 publications
(287 reference statements)
3
87
0
1
Order By: Relevance
“…18,59,61,62 Interestingly, many studies suggest that microvilli protrusions are critical for mediating interactions between KG1a cells in flow and selectins (or endothelial cells). The microvilli undergo extensions and may form tethers, [63][64][65][66][67][68][69] so if these structures are eliminated by the knockdown of CD34, this would likely explain the effect on cell rolling. Furthermore, these data are in agreement with previous flow-based studies that showed that CD34 isolated from lysates of KG1a cells bound CHO-E cells 17 and that mouse thymocytes ectopically expressing CD34 specifically bound to human BM endothelial cells where control thymocytes not expressing CD34 did not.…”
Section: Discussionmentioning
confidence: 99%
“…18,59,61,62 Interestingly, many studies suggest that microvilli protrusions are critical for mediating interactions between KG1a cells in flow and selectins (or endothelial cells). The microvilli undergo extensions and may form tethers, [63][64][65][66][67][68][69] so if these structures are eliminated by the knockdown of CD34, this would likely explain the effect on cell rolling. Furthermore, these data are in agreement with previous flow-based studies that showed that CD34 isolated from lysates of KG1a cells bound CHO-E cells 17 and that mouse thymocytes ectopically expressing CD34 specifically bound to human BM endothelial cells where control thymocytes not expressing CD34 did not.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a growing body of evidence has accumulated from the study of shear-dependent adhesion of other haematopoietic cells, particularly neutrophils 40,41 , that dynamic changes in the plasma membrane, some of which involves membrane reserves, have a profound impact on cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, this adhesion is mediated by catch-bond-like interactions 12,13 between P- 14 and E-selectins 15 expressed on endothelial cells lining blood vessels and P-selectin glycoprotein ligand-1 (PSGL-1) found at microvilli tips of leukocytes 16 . Despite our understanding of the individual components, how the molecular details of adhesion bonds scale to cell-surface adhesion and rolling behavior remains poorly understood 2,17,18 . Here, we developed a label-free method that maps the functional adhesion sites and strengths on a cell surface as it rolls across a surface coated uniformly with adhesion receptors.…”
mentioning
confidence: 99%